Enzymatic alternatives to permanent hair straightening methods - Ford, Candice (2023)
Permanent hair straightening is a highly popular treatment, especially among African hair types. However, current methods rely on the use of harsh chemicals, such as sodium hydroxide or formaldehyde, and are associated with a range of health concerns, including hair breakage, loss and severe scalp disorders. Permanent hair straightening treatments usually involve a disulfide bond-breaking step which allows the opening of the hair structure, followed by mechanical hair straightening and crosslinking, which helps to set the new hair morphology. In recent years, the cosmetic sector has seen the development of a considerable range of biotechnologically-derived active agents, which offer biocompatibility, versatile activity and good performance. This project explores the feasibility of incorporating enzymes, which exhibit relevant disulfide bond-reducing and crosslinking activities in nature, into milder permanent hair straightening treatments. The thioredoxin system from Bacillus subtilis was identified as a potential alternative for breaking disulfide bonds in keratins. The enzymes thioredoxin and thioredoxin reductases were expressed and purified in E. coli. Thioredoxin activity was initially assessed on KeratecTM IFP, a solubilised wool keratin substrate bearing a mix of cystine and sulfonated thiol motifs, associated with easier enzymatic keratin penetration than insoluble counterparts. Reduced thioredoxin was regenerated either by DTT or thioredoxin reductase and NADPH, as electron donors. The reduction of S-sulfocysteine and disulfide bonds in soluble keratin by thioredoxin was observed both by Ellman’s and NADPH assays, which monitor free thiols and NADPH consumption, respectively. However, disulfide bond reducing activity was not observed using solid human hair keratin, despite attempts to improve substrate availability through treatment with keratinase from Bacillus licheniformis and swelling agents, such as urea. Enzymatic keratin crosslinking was then studied using laccase from Trametes versicolor, tyrosinase from mushroom and microbial transglutaminase, all well characterised crosslinking enzymes with activity on proteins and currently used in a range of industries (eg. food, textile). Soluble keratin crosslinking by laccase was observed using size-exclusion chromatography (SEM) and sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS PAGE), both in the presence and absence of vanillin and acetosyringone mediators. However, a lack of significant enzymatic crosslinking was noted for solid hair keratin, where no change in tensile strength was observed upon treatment with laccase. Overall, novel enzymatic reducing and crosslinking modifications were successfully carried out on solubilised keratin. However, challenges remain regarding solid hair keratin, associated with poor substrate availability and enzyme penetration.